2005
DOI: 10.1080/10408440591007133
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Using Mode of Action and Life Stage Information to Evaluate the Human Relevance of Animal Toxicity Data

Abstract: A complete mode of action human relevance analysis--as distinct from mode of action (MOA) analysis alone--depends on robust information on the animal MOA, as well as systematic comparison of the animal data with corresponding information from humans. In November 2003, the International Life Sciences Institute's Risk Science Institute (ILSI RSI) published a 2-year study using animal and human MOA information to generate a four-part Human Relevance Framework (HRF) for systematic and transparent analysis of MOA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(108 citation statements)
references
References 4 publications
0
107
0
Order By: Relevance
“…Mode of action (MOA) is increasingly being considered in the risk assessment of pesticides� During the past decade, the International Life Sciences Institute (ILSI) and the International Programme on Chemical Safety (IPCS) of the World Health Organization (WHO) have been evolving a framework for the analysis of mode of action for rodent toxicity and carcinogenicity findings along with assessment of their human relevance (Sonich-Mullin et al�, 2001;Meek et al�, 2003;Seed et al�, 2005;Boobis et al�, 2006Boobis et al�, , 2008� Numerous case studies have been published illustrating the applicability of the framework for genotoxic and nongenotoxic cancer modes of action and for cancer and noncancer endpoints� Mode of action analysis has been incorporated into the risk assessment guidelines of various regulatory agencies, including the US Environmental Protection Agency (US EPA, 2005)� Folpet and captan are used for their fungicidal properties in both industrial and agricultural products� Their structures are shown in Figure 1 along with their reaction with thiols� Both compounds have Reregistration Eligibility Decisions (REDs) issued (US EPA 1999a, 1999b as well as subsequent reviews (US EPA 2003, 2004a, 2004b) that included the reclassification of captan from "B2" (probable human carcinogen) to "not likely" at dietary exposures expected from agricultural use (US EPA, 2004a;Gordon, 2007)� The major tumor finding from captan bioassays was gastrointestinal adenomas and adenocarcinomas in mice, primarily in the duodenum� By contrast, there was no carcinogenic effect of captan in rats� The 2004 cancer reclassification was based on the 1999 proposed Carcinogenic Risk Assessment guidelines (US EPA, 1999c) that were finalized in 2005 (US EPA, 2005)� Folpet, chemically and biologically similar to captan, has also been evaluated in rodent carcinogenicity bioassays and has a similar pattern of tumor development, that is, gastrointestinal tumors in mice and the absence of treatmentrelated tumors in rats� Studies evaluating the early stages of effects in the gastrointestinal tract support analysis of the mode of action� Folpet provides an example of how the application of the ILSI/IPCS mode of action and human relevance framework can be applied to tumors in assessing possible carcinogenic risk to humans� Folpet previously was considered by EPA a genotoxic carcinogen, like captan, and was considered a carcinogen in mice and rats (Quest et al�, 1993)� Given the information available concerning mode of action, assessment of human relevance and the precedent setting case of captan, folpet today would likely be classified as a nongenotoxic, threshold-based carcinogen, with carcinogenicity only in mice� We describe below the basis for concluding that the rat bioassays are negative; this has also been the conclusion of Joint Food and Agriculture Organization of the United Nations (FAO/WHO) Meeting on Pesticide Residues (JMPR) (FAO/WHO, 1996) and European Food Safety Au...…”
Section: Introductionmentioning
confidence: 99%
“…Mode of action (MOA) is increasingly being considered in the risk assessment of pesticides� During the past decade, the International Life Sciences Institute (ILSI) and the International Programme on Chemical Safety (IPCS) of the World Health Organization (WHO) have been evolving a framework for the analysis of mode of action for rodent toxicity and carcinogenicity findings along with assessment of their human relevance (Sonich-Mullin et al�, 2001;Meek et al�, 2003;Seed et al�, 2005;Boobis et al�, 2006Boobis et al�, , 2008� Numerous case studies have been published illustrating the applicability of the framework for genotoxic and nongenotoxic cancer modes of action and for cancer and noncancer endpoints� Mode of action analysis has been incorporated into the risk assessment guidelines of various regulatory agencies, including the US Environmental Protection Agency (US EPA, 2005)� Folpet and captan are used for their fungicidal properties in both industrial and agricultural products� Their structures are shown in Figure 1 along with their reaction with thiols� Both compounds have Reregistration Eligibility Decisions (REDs) issued (US EPA 1999a, 1999b as well as subsequent reviews (US EPA 2003, 2004a, 2004b) that included the reclassification of captan from "B2" (probable human carcinogen) to "not likely" at dietary exposures expected from agricultural use (US EPA, 2004a;Gordon, 2007)� The major tumor finding from captan bioassays was gastrointestinal adenomas and adenocarcinomas in mice, primarily in the duodenum� By contrast, there was no carcinogenic effect of captan in rats� The 2004 cancer reclassification was based on the 1999 proposed Carcinogenic Risk Assessment guidelines (US EPA, 1999c) that were finalized in 2005 (US EPA, 2005)� Folpet, chemically and biologically similar to captan, has also been evaluated in rodent carcinogenicity bioassays and has a similar pattern of tumor development, that is, gastrointestinal tumors in mice and the absence of treatmentrelated tumors in rats� Studies evaluating the early stages of effects in the gastrointestinal tract support analysis of the mode of action� Folpet provides an example of how the application of the ILSI/IPCS mode of action and human relevance framework can be applied to tumors in assessing possible carcinogenic risk to humans� Folpet previously was considered by EPA a genotoxic carcinogen, like captan, and was considered a carcinogen in mice and rats (Quest et al�, 1993)� Given the information available concerning mode of action, assessment of human relevance and the precedent setting case of captan, folpet today would likely be classified as a nongenotoxic, threshold-based carcinogen, with carcinogenicity only in mice� We describe below the basis for concluding that the rat bioassays are negative; this has also been the conclusion of Joint Food and Agriculture Organization of the United Nations (FAO/WHO) Meeting on Pesticide Residues (JMPR) (FAO/WHO, 1996) and European Food Safety Au...…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these initiatives have been aimed at reducing the unnecessary toxicity testing; however, it is also becoming more common for PPPs to be tested beyond the " standard " requirements and incorporate investigative studies such as MoA to facilitate better characterization of the underlying hazard characteristics to inform the risk assessment and risk management decisions. The MoA/Human Relevance Framework (HRF) developed by the International Programme on Chemical Safety of the World Health Organization , Sonich-Mullin et al 2001 and ILSI , Seed et al 2005 can be used as a template upon which to elucidate the human relevance of eff ects observed in animals. This paper, along with the companion papers , discusses the application of the MoA/HRF approach to a recently registered active substance, sulfoxafl or (CAS# 946578-00-3;XDE-208, X11422208, XR-208, [1-(6-Trifl uormethylpyridin-3-yl)ethyl)](methyl)-oxido-l 4 -sulfanylidenecyanamide).…”
Section: Historymentioning
confidence: 99%
“…A number of national and international efforts have focused on identifying the mode of action in evaluating the relevance of animal data in humans (Sonich-Mullen et al, 2001;Meek et al, 2002;Seed et al, 2005;USEPA, 2005a). Most of these efforts have focused on the importance of mode of action-based approaches in the risk assessment of carcinogens .…”
Section: 33mentioning
confidence: 99%
“…This framework provides a structured approach for evaluating all data pertaining to the animal mode of action followed by all data relevant to the human mode of action. Recently, considerable efforts are also under way to develop mode of action approaches for toxic end-points other than cancer (Seed et al, 2005). The availability of mode of action information will improve the extrapolation of animal data and relevant human data in risk assessment approaches.…”
Section: 33mentioning
confidence: 99%